Bmp4 signaling is required for outflow-tract septation and branchial-arch artery remodeling - Liu, Wei (National Academy of Sciences, 2004)
The Bmp4 signaling molecule is expressed in ventral splanchnic and branchial-arch mesoderm and outflow-tract (OFT) myocardium, suggesting a role for Bmp4 in OFT development. Inactivation of Bmp4 in the caudal branchial arch and splanchnic mesoderm and OFT myocardium by using a conditional null allele of Bmp4 and the Nkx2.5(cre) recombinase allele resulted in abnormal morphogenesis of branchial-arch arteries (BAAs) and defective OFT septation. Expression of aortic-sac myocardial markers was reduced and expression of the sm22(LacZ) transgene, a smooth-muscle marker, was attenuated in BAAs and conotruncus of Nkx2.5(cre); Bmp4 conditional mutants. Moreover, we found tissue-specific functions for Bmp4 in the regulation of cellular proliferation and apoptosis. We also demonstrate a strong genetic interaction between Bmp4 and Bmp7 in OFT development. Our findings uncover a previously uncharacterized function for Bmp4 in vascular remodeling of the BAAs, and they show definitively that Bmp4, in cooperation with Bmp7, has a central role in OFT septation.